Design, analysis and Reasoning about Tools: Abstracts from the Second Workshop (Aalborg, 1992, 20-21 August) - Nielson, Flemming (DAIMI Report Series, 1992)
The second DART workshop took place on August 20-21, 1992 in Aalborg. The primary aim of the workshop was to increase the awareness of DART participants for each other’s work, and to stimulate cooperation between the various groups. This report contains a brief overview of DART as well as abstracts of the 20 talks given at the workshop and a status report of DART as of summer 1992.